THE UTILITY OF MRI IN CLINICAL DECISION-MAKING FOR PEDIATRIC ATHLETES WITH SYMPTOMATIC SUBFIBULAR OSSICLES. Issue 4 (28th April 2020) - Gamble, James G.; Chan, Charles M; Rinsky, Lawrence A; Frick, Steven L.; Shea, Kevin G.
Background: Pediatric athletes commonly sustain inversion-type ankle fractures. 1, 2 Approximately 1% will form post-traumatic subfibular ossicles (SO), especially after tip avulsion fractures. 3, 4 Athletes with SOs can have pain and recurrent sprains. 5, 6, 7 Here we show the utility of magnetic resonance imaging (MRI) in clinical decision-making for athletes with ankle symptoms and the presence of a SO. Our hypothesis is that MRI can predict which athletes have a stable SO and will respond to non-operative management, and which athletes have an unstable SO and will need surgery. Methods: We performed an IRB approved retrospective cohort study. Children were eligible from our practices if (1) they had radiographic evidence of a SO, (2) they had symptoms of pain and recurrent sprains, and (3) they had undergone MRI during their clinical evaluation. We identified 19 eligible children (20 ankles;) eight girls and eleven boys, ages 5–19 years. Nine involved the left ankle; 11 the right ankle. Most frequent sport was soccer (12/16) followed by basketball (3/14.) From the radiograph we determined ossicle size and location. MRI images were considered positive if fluid-sensitive sequences showed a high-intensity signal between the SO and the fibular epiphysis. Main outcome was treatment (non-surgical or surgical) relative to the MRI findings. Results: Size shape and location: Size and shape were variable. Width ranged from 2 – 10.4 mm and length from 4 – 13.5 mm. Concerning location all were in the distal 1/3 pf the epiphysis. Six were anterior and 14 were anterior-inferior to the fibular tip. MRI findings: Sixteen of the 20 ankles (80%) had positive MRI findings (figure 1), and 4 had negative findings (figure 2). The ATFL attached directly to the fragment in 11 of the 16 MRI positive ankles. Clinical decision making: All athletes with negative MRI findings responded to non-operatively management. Ten of the 16 ankles with positive MRIs have had surgery. Eight had excision of the ossicle and two had internal fixation based on the size of the ossicle. Surgical findings confirmed attachment of the ATFL to the fragment (figure 3.) Six athletes with positive MRIs continue to be under observation. Conclusions: The results support our hypothesis that MRI has predictive value in clinical decision-making for symptomatic athletes with a SO. When fluid-sensitive MRI sequences show high signal intensity between the ossicle and the fibular epiphysis, and when the ATFL attaches to the ossicle, the athlete has a poor prognosis for non-operative management. : Figure 1. Seventeen-year-old with positive MRI who had internal fixation of the fragment Figure 2. Note direct attachment of the ATFL to the mobile SO. References: Su AW, Larson AN. Pediatric ankle fractures: Concepts and treatment principles. Foot Ankle Clin. 2015;20(4):705-719. Pommering TL, Kluchurosky L, Hall SL. Ankle and foot injuries in pediatric and adult athletes. Prim Care 2005;32(1):133-161. Han SH, Choi WJ, Kim S, Kim S-J, Lee JW. Ossicles associate with chronic pain around the malleoli of the ankle. 2008;90-B:1049-1054. Gamble JG, Sugi M, Tileston KR, Chan CM, Livingston KS. The natural history of type VII all-epiphyseal fractures of the lateral malleolus. Orthop J Sports Med. 2019; 7(3) (suppl 1) DOI 10.1177/2325967119S00116. Pill SG, Hatch M, Linton JM, Davidson RS. JBJS 2013;95: e115(1-6). Han SH, Choi WJ, Kim S, Kim SJ, Lee JW. Ossicles associated with chronic pain around the malleoli of the ankle. J Bone Joint Surg Br. 2008;90(8):1049-1054. Danielsson LG. Avulsion fracture of the lateral malleolus in children. Injury 12:165-167